Dual‐Purpose 3D‐Silica Nanostructure Matrix for Rapid Epigenetic Reprogramming of Tumor Cell to Cancer Stem Cell Spheroid. Issue 1 (24th November 2022) - Verma, Anish Hiresha; Haldavnekar, Rupa; Venkatakrishnan, Krishnan; Tan, Bo
Abstract: Cancer stem cells (CSCs), a rare subpopulation responsible for tumorigenesis and therapeutic resistance, are difficult to characterize and isolate. Conventional method of growing CSCs takes up to 2–8 weeks inhibiting the rate of research. Therefore, rapid reprogramming (RR) of tumor cells into CSCs is crucial to accelerate the stem cell oncology research. The current RR techniques cannot be utilized for CSC RR due to many limitations posed due to isolation requirements resulting in loss of vital data. Hence, a technique that can induce CSC RR without the need for isolation procedures is needed. Here, fabrication of a 3D‐silica nanostructured extracellular matrix for RR and in situ monitoring is reported. The RR is tested using three preclinical cancer models. The 3D matrix and a zeta potential study confirm an intense material‐cellular interaction resulting in the enhanced expressions of surface and epigenetic biomarkers. Cancer cells require only 3‐day period to form CSC spheroids with 3D‐silica extracellular matrix. Real‐time single‐cell monitoring of the methylene blue‐induced photodynamic demonstrates the dual functionality. To the authors' knowledge, this is the first study to demonstrate a CSC epigenetic reprogramming using nanostructures. These findings may pave the path for accelerating the stem cell research in oncology. Abstract : Rapid reprogramming (RR) of tumor cells into cancer stem cells (CSC) is a crucial strategy to accelerate Research and Development in stem cell oncology. Here, dual purpose 3D‐nano silica matrices for RR and real time monitoring are reported. The nanostructure induce intense material–cellular interaction resulting in RR, elevating expressions of surface and epigenetic biomarkers as well as surface‐enhanced Raman spectroscopy biomolecular profiling in real‐time.